Inheritance and AFLP Tagging of Leaflet Mutants in Mungbean (Vigna radiata (L.) Wilczek) - Rudy Soehendi; Sontichai Chanprame; Theerayut Toojinda; Peerasak Srinives (Agriculture and Natural Resources, 2006)
Leaflet type is a canopy characteristic related to light interception, thus modification of canopy structure can alter seed yield. Two multiple leaflet mutants were obtained from gamma-rays irradiation and used in studying the mode of inheritance and tagging with AFLP marker. The cross between largeheptafoliate leaflet with small-pentafoliate leaflet mutants gave all F1 plants with normal trifoliate leaflets. The F2 plants segregated in a 9:3:3:1 ratio of large-trifoliate: large-heptafoliate: small-pentafoliate: small-heptafoliate plants, suggesting that the genes controlling leaflet size and leaflet number were independent loci. The gene symbols N1,n1 and N2,n2 were proposed to control leaflet number. Since there was no plant found with large-pentafoliate leaflets, it was hypothesized that the N2 allele expressed pleiotropic effect on both leaflet number and leaflet size. Thus the genotypes of the above-mentioned F2 could be assigned as N1_N2_, n1n1N2_, N1_n2n2, and n1n1n2n2, respectively. Another possibility was that there was another locus with S and s alleles controlling the leaflet size and tightly linked with N2 and n2, respectively. There were 3 AFLP markers linked to number of leaflets per leaf and all of them corresponded to the N1 allele of the small-pentafoliate parent.